Effects of E-health-based interventions on glycemic control for patients with type 2 diabetes: a Bayesian network meta-analysis - Zhang, Xiaoyue; Zhang, Lanchao; Lin, Yuxin; Liu, Yihua; Yang, Xiaochen; Cao, Wangnan; Ji, Ying; Chang, Chun (Frontiers in Endocrinology, 2023)
The high disease burden of type 2 diabetes seriously affects the quality of survival of patients, and with the deep integration of the Internet and healthcare, the application of electronic technology to disease management has become a trend. The aim of this study was to evaluate the effectiveness of different forms and duration of E-health interventions on type 2 diabetes patients' glycemic control.PubMed, Embase, Cochrane, and Clinical Trials.gov were searched for randomized controlled trials using different forms of E-health intervention on glycemic control in type 2 diabetes patients, including comprehensive measures (CM), smartphone applications (SA), phone calls (PC), short message service (SMS), websites (W), wearable devices (WD), and usual care. The inclusion criteria were: (1) adults (age≥18) with type 2 diabetes mellitus; (2) intervention period ≥1 month; (3) outcome HbA1c (%); (4) randomized control of E-heath approaches. Cochrane tools assessed the risk of bias. R 4.1.2 was used to conduct the Bayesian network meta-analysis. A total of 88 studies with 13,972 type 2 diabetes patients were included. Compared to the usual care group, the intervention with SMS was superior in reducing HbA1c level (mean difference (MD)-0.56, 95% confidence interval (CI): -0.82 to -0.31), followed by SA (MD-0.45, 95%CI: -0.61 to -0.30), CM (MD-0.41, 95%CI: -0.57 to -0.25), W (MD-0.39, 95% CI: -0.60 to -0.18) and PC (MD-0.32, 95%CI: -0.50 to -0.14) (P < 0.05). Subgroup analysis revealed that interventions ≤6 months were most effective. Any type of E-health can improve glycemic control in type 2 diabetes patients. SMS is a high frequency, low barrier technology which achieves the best effect in lowering HbA1c, with <6 months being the optimal intervention duration.